Resislance in grasses tolhe paslure spultlebug. - Cosenza, Gilson Westin; Andrade, Ronaldo Pereira De; Gomes, Darci Tercio; Rocha, Carlos Magno C. Da (Pesquisa Agropecuaria Brasileira, 2013)
The levei of resistance ol grasses tolhe spittlebug, Doeis ifavopicta (Stal 1854), wastezied under field cendifions. Tho most resistant grasses were: Andropogon gayanus cv. Planaltina, Brachia ria brizantha cv. Marandu, Cynodon plectostachyus, I -liparrhenia rufa, and Panicun, maximum cv. TobiatL The most suecepliblo were Brachiaria ruziziensis and 8. decumbens. Teste lo determine lhe mechanism ol resistance and basis for resistance 01 lan grasses wero developed under saeened cages and iaboratoty conditions. The mechanisms 01 resistance ot C. plectostachyus and H. rufa are probably antixenosis and atibiosis A. gayanus and B. brizantha cv. Marandu display probably antixenosis, antibiosis and tolerance; P. maximum cv. Tobiatã and B. humidicola display tolerance. B. decun,bens and B. ruziziensis showed te be lhe most susceplible of Dia studied grasses and did not show any mechanisni of resistance. Pasturo management showed lo be an important [actor on spiwebug controL Keeping lhe pastures of susceptible grasses tali during spittlebug season and using lhe resistant grasses during this time demonstrated lo provide lhe contraI aI lhe pest.